Perancangan Sistem Informasi Pengarsipan Dokumen pada Mahkamah Syar’iyah Kota Banda Aceh - Khairul Rahmadi (KITA Institute, 2020)
At the Syar'iyah Court of Banda Aceh City, the archiving information system within the agency could be said to be inefficient because there were still many conventional filing information systems applied, namely storing in filing cabinets, and recording to books so that accuracy could still be said to be unfavorable. When viewed in terms of space, it requires an inventory of places for equipment such as filing cabinets, maps, shelves, and others. While in terms of time, the search for the arrangement of documents that are not neat. In terms of cost, the need for care and maintenance of archive storage. The formulation of the problems in this study can be formulated; Designing the Document Filing Information System at the Banda Aceh Syar'iyah Court, Is the Banda Aceh City Syar'iyah Court Filing Information System the information used will be faster and more accurate, and How to present the Syar'iyah Court Document Filing Information System. The method used in designing the NET Document Filing Information System at the Banda Aceh Syar'iyah Court is to use the waterfall method or the waterfall method. Data collection techniques using research methods by observation, interview, and literature study. The tools used are Microsoft Visual Basic .NET as an application in interface design and Microsoft Office Access as a DBMS. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.